I Am, Therefore I Buy: Low Self-Esteem and the Pursuit of Self-Verifying Consumption - Stuppy, Anika; Mead, Nicole L; Van Osselaer, Stijn M J (Journal of Consumer Research, 2020)
Abstract The idea that consumers use products to feel good about themselves is a basic tenet of marketing. Yet, in addition to the motive to self-enhance, consumers also strive to confirm their self-views (i.e., self-verification). Although self-verification provides self-related benefits, its role in consumer behavior is poorly understood. To redress that gap, we examine a dispositional variable—trait self-esteem—that predicts whether consumers self-verify in the marketplace. We propose that low (vs. high) self-esteem consumers gravitate toward inferior products because those products confirm their pessimistic self-views. Five studies supported our theorizing: low (vs. high) self-esteem participants gravitated toward inferior products (study 1) because of the motivation to self-verify (study 2). Low self-esteem consumers preferred inferior products only when those products signaled pessimistic (vs. positive) self-views and could therefore be self-verifying (study 3). Even more telling, low self-esteem consumers’ propensity to choose inferior products disappeared after they were induced to view themselves as consumers of superior products (study 4), but remained in the wake of negative feedback (study 5). Our investigation thus highlights self-esteem as a boundary condition for compensatory consumption. By pinpointing factors that predict when self-verification guides consumer behavior, this work enriches the field’s understanding of how products serve self-motives.